SEXUAL HARASSMENT: LEGAL PROTECTION AGAINTS WORKERS IN MALAYSIA - H. Hanafi Arief (Al-Adl : Jurnal Hukum, 2017)
AbstractSexual harassment is a criminality that the government of Malaysia should give protection to the victims. Malaysia Criminal Act, Employment Act 1955, and Industrial Relations Act 1967 and Regulation or Act 117 were enforced to do. The protection includes any victim living in Malaysia without discrimination citizens or non-citizens, including labour migrants whether documented or undocumented. Sometimes employer violated their worker’s rights because he believes that workers tend not to reveal their irregular and illegal status. Protection via due process and fundamental human rights is embodied in the Malaysia Federal Constitution and applicable to them regardless of their status. This writing is proposed to give discussion on how the Malaysian Acts protect sexual harassment against the workplace workers. Data were obtained through research literature, with the writer trying to discover and collect material from documents, books, laws and regulations that apply specifically to the criminal law in relation to the workplace.